A Graph Knowledge-base for Auditing Human Resources Public Management - Pinto, Fernando Antonio D. G.; Lifschitz, Sérgio; Haeusler, Edward Hermann (Anais do Latin American Symposium on Digital Government (LASDiGov); 2022: Anais do X Workshop de Computação Aplicada em Governo Eletrônico, 2022)
Given the growing volume of data that is generated in the public sector, new payroll audit models are created. Payroll is a sensitive area and requires assertive processes in its operations. The formal verification of public rules, in a knowledge base, aims to demonstrate the conformity of public acts in relation to the respective legal norms. In this paper we build a knowledge base of public acts from the extraction of information contained in a 9-year series of a official gazette. With this, we can audit the participation of public servers in technical committees through SPARQL queries in a knowledge base such as RDF graphs.